Avaliação da durabilidade dos efeitos da mobilização com movimento de Mulligan na hiperalgesia secundária, nos aspectos funcionais e emocionais, em indivíduos com diagnóstico de osteoartrite de joelho - Gomes, Matheus Garcia (2018)
OBJECTIVES: To evaluate the effects of Mobilization with Movement (MWM) on pain, physical function and emotional aspects in individuals with knee osteoarthritis (KOA). METHODS: This is a prospective case series study with a single group of 30 subjects (61.43 ± 6.22) with symptomatic KOA. The protocol involved a previous evaluation, six intervention sessions during two weeks, reassessment 24 hours after intervention, and followed by three further weekly evaluations. The intervention included three MWM techniques. The variables evaluated were pain (Pressure Pain Threshold - PPT and Visual Numeric Scale - VNS), physical function (Range of Movement - ROM, proprioceptive acuity and the Western Ontario and McMaster Universities Osteoarthritis Index – WOMAC) and for emotional aspects the Beck Depression Inventory - BDI. ANOVA for repeated measures was used considering a significance level of 5%. RESULTS: From the first to the second evaluation, statistical differences (p <0.05) were observed for PPT in the rectus femoris (RF), tibialis anterior (TA) and patellar tendon (PT) sites. For VNS, BDI, and WOMAC, significant reductions after intervention (second evaluation) could be observed. In the follow-up, for most variables (except PPTs), it was possible to observe a trend of better final values than the baseline. Moreover, no significant changes were observed for proprioceptive acuity and ROM. CONCLUSION: MWM was effective for pain relief, physical function and emotional aspects of individuals with KOA in the two weeks of treatment. During follow-up, it was possible to observe that final values tended to return at the baseline levels.